Extraction of Astaxanthin from Hyperproducing Haematococcus Pluvialis Using Different Oils - Nisha Tiwari,; Surendra Singh, (International Journal of Scientific Research in Science and Technology, 2025)
Astaxanthin is a high antioxidant which is red carotenoid pigment obtained from many microalgae species. It is an important preservative of the immune system and it is used in the treatment of cancer, skin and heart diseases. The most efficient source of astaxanthin is Haematococcus pluvialis microalgae. The aim of the present investigation was to extract the astaxatnin, a food, a feed and pharmaceutical valuable secondary carotenoid from the Haematococcus pluvialis with common vegetable oils. Without a cell harvest process step, the culture was directly mixed with the vegetable oils; the astaxanthin inside the cell was extracted into the vegetable oil phase by hydrophobic interaction. We have found that the maximum extractability of astaxanthin 98.28 % in soybean oil from mutant strain.
Keywords: Astaxanthin; microalgae Haematococcus pluvialis vegetable oil; extractability